ANALISIS TENTANG PENGETAHUAN MAHASISWA PPKN FKIP UNIVERSITAS RIAU TENTANG 4 PILAR MPR RI - Fauzan Tri Anggara; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is based on the 4 pillars of the MPR RI to analyze theknowledge of PPKn students about the 4 pillars of the MPR RI, which is always carriedout in the Pancasila and Citizenship Education study program every year and isincluded in the annual calendar of the MPR RI. In this study, the component is aboutstudents which as the pillars of a nation's civilization, students have a strong andsuperior character. And to make this happen, apart from having a superior character, itmust also be accompanied by the 4 pillars of nationality so that our nation will be betterthan before by obtaining a developed country and a brighter future for the nation. TheFour Pillars of the MPR RI must continue to be carried out openly with a wider reach,so that students increasingly understand the values of the 4 Pillars of the MPR RI as thefoundation in the life of society, nation and state. The formulation of the problem in thisstudy is how the knowledge of PPKn FKIP students at the University of Riau about the4 Pillars of the MPR RI. This research method is descriptive quantitative, the datacollection instruments used in this research are questionnaires, interviews anddocumentation. The variable of this research is the Analysis of Knowledge of PPKnFKIP Students, University of Riau About the 4 Pillars of the MPR RI. which consists of4 indicators with a total of 23 questions based on Research Instruments. The populationin this study were PPKn FKIP students at the University of Riau with a total populationof 215 people. Sampling of the entire population was taken using the PurposiveSampling technique and to determine respondents consisting of 100 people with 50people from the 2018 class and 50 from the 2019 class. the results of research andrecapitulation that have been carried out by respondent researchers who answeredVery Know (ST) + Know (T) 51.14% + 40.33% = 91.47%. Thus, it can be concludedthat the Analysis of Knowledge of PPKn FKIP Students at the University of Riau aboutthe 4 Pillars of the MPR RI can be categorized as